Veto Players, intertemporal interactions and policy adaptability: How do political institutions work? - Carlos Scartascini; Ernesto Stein; Mariano Tommasi (Inter-American Development Bank, Research Department, 2008)
Veto player theory argues that a higher number of veto players lowers the likelihood of change; in turn, policies that do not change help to sustain commitments but may prevent adaptation to changing circumstances. This paper challenges that claim of veto player theory by arguing that policy stability does not necessarily mean lower policy adaptability. If policymaking takes place over time with actors interacting repeatedly, more cooperative polities might be able to achieve both objectives at once, and a higher number of veto players might even favor intertemporal cooperation. The paper presents a simple formalization of the argument and some supportive cross-national empirical evidence.
Keywords: 330